Fatores associados a ocorrência e impacto econômico das alterações "white striping" e "wooden breast" em frangos de corte - Zanetti, Marcelo Augusto (2016)
The growth of the Brazilian poultry industry in recent years is due to the modernization and the use of instruments such as: proper management, health, balanced diet and breeding. Through breeding of broiler strains, objective industry to produce heavier animals, leading to occurrence of changes, and causing losses to the industry. Among the muscle alterations present in chicken, there are the calls myopathies White Streaks (White Striping) and Chest Wood (Wooden Breast). In this study were collected in the inspection lines of a northern chicken slaughterhouse Rio Grande do Sul, breasts with those amendments, which were not classified according to the degree of myopathy. The birds were the Cobb, males, fitness for cuts, weighing 2160g and 3000g, with 45 to 49 days of life, 12 different lots, totaling 207.000 birds. These lots were collected aviary data, such as age and weight of the birds for slaughter and breeding density in the aviary, and compared with the number of convictions for these myopathies, showing that heavier birds with older, and lower density population have greater condemnation by myopathies. Were also collected 63 chicken breasts sentenced weighing an average of 1800 grams confront such information with the price of kg of the chest, which is R $ 5.90 (as of now) and concluded that 0.8% per day of chicken breasts each batch are disqualified due to such injuries, impacting in a loss of R$ 18.050,40 per day to the industry.